Pengaruh Model Pembelajaran Visual Auditori Kinestetik (VAK) terhadap Hasil Belajar Kognitif Peserta Didik pada Materi Mitigasi Bencana di Kelas XI IPS SMA Negeri 1 Jakarta - Shafa Anis Salsabila; Ilham Badaruddin Mataburu; Lia Kusumawati (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the cognitive learning outcome of the visual, auditory, kinesthetic learning model on eleventh-grade social studies students' in disaster mitigation material at SMA Negeri 1 Jakarta during 2022/2023 academic year. Using a quasi-experimental method with a pretest & posttest control group design, the sample population selected through cluster random sampling, comprises 33 students in control group and 35 students in experimental group. The research instrument consists of 20 items multiple-choice test. The results shows that students learning with the visual, auditory, kinesthetic approach improved significantly, from 57.28 to 77—an increase of 19.71. Meanwhile, those with a cooperative learning method saw a smaller increase, from 57.12 to 64.55—an increase of 7.42. The Independent Sample t Test produced a Sig.(2-tailed) value of 0.001, rejecting null hypothesis and accepting alternative hypothesis. In conclusion, implementing Visual, Auditory, Kinesthetic model positively impacts students' learning outcomes in disaster mitigation material.